Resilient Design Strategy: Engaging Amphibious Structures to Combat Flood in the Development of an Internally Displaced Persons Settlement Scheme in Nigeria. Issue 1 (March 2021) - Sholanke, A. B.; Chilaka, D. A.; Oti, M. A.; Nelson, S. A.; Nnatuanya, M. C.; Udezi, B. E.
Abstract: Flooding is a natural disaster that has been on the increase in many parts of the world. In the last two decades, this unforeseen destructive occurrence has led to the loss of millions of lives and properties valued at millions of dollars in many countries, including Nigeria. Though several attempts have been advanced as possible solutions to help curb the devastating consequences of flooding in the past, many of the solutions have proven not to be as effective as expected. This paper, examined the potentials amphibious structures present as a resilient strategy to combat flood, to develop an architectural design proposal of a sustainable Internally Displaced Persons (IDPs) settlement, that can withstand the peculiar challenges caused by flooding in Nigeria. The study adopted qualitative research approaches. Data consulted to develop the design proposal were assembled through random search of the internet from archival documents related to the subject and the data were analysed by thematic textual analysis. The findings were presented with texts, architectural two-dimensional and 3-dimensional drawings, tables and plates. Useful information from the analysed data became the conceptual framework on which the scheme was developed. The outcome of the study is the development of an architectural design scheme that utilised a combination of amphibious structures strategy and simple sustainable innovative design measures to proffer solution to an environmental problem, as well as the peculiar social, cultural and religious issues associated with the study area. The conceptual base on which the model was developed is for the settlement to co-exist with flood, rather than the common concept of resisting flood. Though the design was developed for a location in Girei, Adamawa State in the Northern part of Nigeria, the scheme is a useful guide for designing settlements and addressing issues in flood-prone areas in other parts of the globe, as well as a valuable educational material on issues pertaining to the development of settlements in flood-prone areas.